PENGARUH BIMBINGAN MENTAL TERHADAP PERILAKU AGRESIF PADA REMAJA DI RUMAH TAHANAN MALENDENG KECAMATAN TIKALA MANADO - Maria Terok; Tinneke A. Tololiu; Henceslaus Palit (Jurnal Ilmiah Perawat Manado (Juiperdo), 2014)
The increasing of juvenile aggressive behavior in Malendeng penitentiary house of Manado city is cause by their incapable to solve their problems. Juvenile inmates are mostly easy get irritated when being humiliate by bad words or mocking done by fellow inmate and burst into anger when being provoked and also no remorse is shown when doing a mistake. The inmate will very much angry when their will is being against, they felt worthless and stubborn, and there’s grudge and urge to take revenge for bad things happen to other around them. Type of this research is experimental research with vague treatment design (Quasi Experimental), by pre-test and post-test group design. Number of sample is 50 respondents which being choose with a simple random sampling. Measurement of aggressive behavior alteration is using Agitated Behavior Scale (ABS) questioner from Ohio State University in Colombus. This analysis is using T test assessment. The result of analysis on aggressive behavior in pre-test shows that 36 respondents (72%) experiencing mid aggression while within penitentiary house and 6 respondents (12%) experiencing heavy aggression. After giving a mental guidance to those juvenile inmates, a significant change occurs. This being found in post-test result which shows 46 respondents (92%) not experiencing aggression and only small part of them which is 4 respondents (8%) still experiencing mild aggression while mid and heavy aggression is being solved. Conclusion of statistic assessment result of T test then point out a hypothetical result P= 0, 00 < 0, 05 which means Ha is accepted. This result then reveals the effect giving a mental guidance to juvenile inmates toward to declining aggressive behavior. Suggestion that hopefully the juvenile inmates in Malendeng penitentiary house of Manado city, can apply the mental guidance given to them